Maternal time investment in caregiving activities to promote early childhood development: evidence from rural India - Batura, Neha; Roy, Reetabrata; Aziz, Sarmad; Sharma, Kamalkant; Kumar, Divya; Verma, Deepali; Correa Ossa, Ana; Spinola, Paula; Soremekun, Seyi; Sikander, Siham; Zafar, Shamsa; Divan, Gauri; et al. (Frontiers in Pediatrics, 2023)
Intervention strategies to improve early childhood development are often targeted at primary caregivers of children, usually mothers. Interventions require mothers to assimilate new information, act upon it, and adopt development promoting behaviors. However, women face competing demands return to familiar behaviors. We explore mothers’ time allocation to caregiving activities for young children, within a cluster randomised controlled trial of a nutrition and care for development intervention in India. We collected quantitative maternal time use data from 704 mothers when their child was 12 months old, and 603 mothers when their child was 18 months old. We test for significant differences at both time points between arms as well as over time, using linear regression, adjusting for clusters using random effects. We find no statistically significant difference between arms. On average, mothers spent most time on household chores at both time points (6.5 hours). When children were aged 12 months, 3.5 hours were spent on childcare activities. At 18 months of age, mothers spent more time on income generating activities (30 minutes), and on leisure (4.5 hours). When children were 18 months old, less time was spent on feeding/breastfeeding children and playing with children, but more time was spent talking or reading to children at 18 months. Within a short period of time in early childhood, maternal time use can change, with allocations being diverted away from childcare activities to others. This suggests that changing maternal time allocation in resource-poor households may be challenging and inhibit uptake of new/optimal behaviors.